The effect of the use of virtual reality technology on the course of the perioperative period during cesarean section - O. V. Ryazanova; S. M. Makishev; G. V. Grinenko; N. Yu. Pylaeva; K. I. Korolev; S. A. Kolominchuk; M. D. Nagulmanova; A. A. Ryazanova (Вестник анестезиологии и реаниматологии, 2025)
Introduction. Cesarean section is associated with a significant level of emotional stress. Given the inability to use most anxiolytic drugs in obstetrics, alternative methods for stabilizing the psycho-emotional state of patients are required. One possible option is virtual reality technology. The objective was to evaluate the impact of virtual reality technology on perinatal anxiety and pain intensity during elective cesarean section.Materials and Methods. A prospective randomized controlled trial was conducted with 62 patients. The patients were divided into two groups: the control group (n = 30) and the main group (n = 32). In the control group, standard preoperative preparation was performed, while in the main group, virtual reality technology was additionally used. Anxiety levels were assessed using the PASS-R scale, and pain intensity was evaluated using the visual analog scale (VAS). Additionally, blood pressure and heart rate indicators were analyzed. Results. Compared to the control group, the use of virtual reality technology resulted in a significant reduction in anxiety levels 6 hours after surgery (11.2 ± 4.9 vs. 17.4 ± 5.8 points, p < 0.05) and a decrease in pain intensity during fetal extraction (2.5 ± 1.3 vs. 4.0 ± 1.3 points, p = 0.0089). The main group also showed lower blood pressure and heart rate indicators compared to the control group at all stages of the surgical intervention (p < 0.05).Conclusion. The use of virtual reality technology before and during elective cesarean section under spinal anesthesia may be an effective method for reducing anxiety, stress, and pain during surgery and in the postoperative period, as well as for improving the psychological state of patients.